2012
DOI: 10.1002/lt.23379
|View full text |Cite
|
Sign up to set email alerts
|

Duration of red blood cell storage and outcomes following orthotopic liver transplantation

Abstract: Liver transplantation may be complicated by massive intraoperative bleeding, and red blood cell (RBC) transfusions may be required. The storage duration or age of transfused RBCs has been shown to affect the morbidity and mortality of critically ill, trauma, and cardiac surgery patients. Here we investigate the effect of RBC age on the outcomes of liver transplant patients. Five hundred thirty-one patients underwent orthotopic liver transplantation between January 1, 2000 and August 15, 2010. The patient demog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
44
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(47 citation statements)
references
References 41 publications
1
44
2
Order By: Relevance
“…The median [interquartile range] storage time of and 15 [11][12][13][14][15][16][17][18][19][20] days in fresh blood and in old blood groups, respectively. The occurrence of postoperative infection did not differ between groups (fresh blood 22% vs. old blood 25%; relative risk [RR], 1.17; confidence interval [CI], 0.71-1.93), although wound infections occurred more frequently in old blood (15% vs. 5%; RR, 3.09; CI,).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The median [interquartile range] storage time of and 15 [11][12][13][14][15][16][17][18][19][20] days in fresh blood and in old blood groups, respectively. The occurrence of postoperative infection did not differ between groups (fresh blood 22% vs. old blood 25%; relative risk [RR], 1.17; confidence interval [CI], 0.71-1.93), although wound infections occurred more frequently in old blood (15% vs. 5%; RR, 3.09; CI,).…”
Section: Resultsmentioning
confidence: 99%
“…There were no other differences in the secondary outcomes between groups in the ITT analysis. In the AT analysis, hospital LOS was longer in the old blood group than in the fresh blood group (11 [7][8][9][10][11][12][13][14][15][16][17][18][19][20] vs. 9 [6][7][8][9][10][11][12][13][14][15][16]; difference in means, -3.62; CI, -7.6 to -0.6; Table 4). …”
Section: Secondary Outcomesmentioning
confidence: 99%
See 1 more Smart Citation
“…[16][17][18] Several investigations have reported that massive intraoperative allogeneic red blood cell transfusions have a negative effect on liver transplant recipient outcomes. [19][20][21] Ramos and associates 22 confirmed that massive red blood cell transfusions are associated with longer hospital stays, and decreased postoperative survival for liver transplant recipients. Benson and associates 23 suggest that red blood cells transfusion contributes to postoperative infections in a dose-dependent manner.…”
Section: Discussionmentioning
confidence: 96%
“…Studies demonstrated increased rates of mortality [22][23][24][25][26][27][28], morbidity [29], MOD [22,27,30] and infection [22,31,32] in trauma, cardiac surgery, cardiovascular and ICU patients receiving blood stored for two weeks or more. On the other hand, several other studies were unable to demonstrate that the storage duration of blood components utilised have contributed to adverse patient outcomes [24,[33][34][35][36][37][38][39].…”
Section: Clinical Outcomes Of Prbc Transfusionmentioning
confidence: 99%